HOUSING AND BREEDING PACTICES FOLLOWED BY PROFESSIONAL GIR CATTLE OWNERS OF ANAND DISTRICT - Divekar , B S; Saiyed , L H (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Data were collected from 100 professional Gir cattle owners from rural area covering 12 villages in Anand, Borsad and Umreth talukas of middle Gujarat which are densely populated with this community. The information was collected from respondents on housing and breeding management of dairy animals by a questionnaire. Majority of professional Gir cattle owners were landless and 94 % of them tied their animals in front of house on kuccha floor without providing shed/roof. Normally on an average length and width of floor space provided to animal was 7.0 ft and 3.55 ft. Housing management practices adopted in majority of cases were unhygienic, unhealthy and not according to the scientific recommendation. All (100.00 %) Gir owners surveyed followed natural method of breeding. Majority of Gir owners identified their animals in estrus by signs of mounting (53.00 %) followed by bellowing (49.00 %), frequent urination (13.00 %) and uneasiness (3.00 %). Majority (83.00 %) of them did not get confirmed the pregnancy in their animals. Majority (80.00 %) of the Gir owners had no knowledge about the signs of parturition. 42 per cent of them faced abortion as the major abnormality during calving followed by prolapse (34.00 %) and placental retention (22.00 %).